The Effect of Problem Based Learning Based on Multiple Representations on Ecosystem Material in Class X on Problem Solving Ability by Students. - Wahyuni, Eki; Mubarok, Ibnul (Universitas Negeri Semarang, 2024)
The skills that can be developed through education are 21st century skills, including the ability to solve problems related to issues faced in everyday life. Therefore, students need to be taught problem solving by using PBL model based on multiple representations on ecosystem material. The purpose of this study was to analyze the effect of PBL based on multiple representations in class X ecosystem material on students' problem solving skills. The research design used is an experiment with the quasi experiment method. The population in this study were all grade X students at SMAN 14 Semarang in the 2023/2024 school year. Sampling in this study using purposive random sampling technique based on the teacher's consideration that the selected class has a balanced ability. Two classes were sampled, namely class X5 as the experimental class which was given treatment using PBL model based on multiple representations and X9 as the control class which was given treatment using PBL model without multiple representations. Based on the results of the research, students' problem solving skills have increased in both experimental and control classes. The N-Gain test results of the experimental class are 0.3661 which means an increase in problem solving ability is moderate, while the N-Gain results of the control class are 0.1544 which means an increase in problem solving ability is low. The T-test results show that there is a significant difference between the average pretest-posttest scores in the experimental class and a significant average difference between the posttest scores in the experimental and control classes. The results of the Spearman Rank correlation test show that the Sig. (2-tailed) 0.880>0.05 which means that the application of PBL based on multiple representations has no effect on students' problem solving skills on ecosystem material. This can be influenced by several factors, namely the PBL model used, the formation of discussion groups, and also the number of multiple representations taught to students.